Possible Pathogenic Bacteria Present on Stumps of Amputees Applying Prostheses: A Case of Mulago National Referral Hospital, Uganda. - Sulaiman Kakooza; Kizito Muwonge (Student's Journal of Health Research, 2021)
Background:  The number of amputees using prostheses is decreasing, and the victims complain that prostheses make stumps itchy and cause sores and they thus opt to go without artificial limbs. This has led to increased joblessness among persons with orthopedic disabilities. This research, therefore, sought to determine whether the prostheses increase the number of species of bacteria found on the stumps of amputees since bacteria are known to be the primary cause of the discomfort in form of itches and sores.  Methodology:  Thirty participants were selected for this study, and were divided into two groups; 22 candidates were in the experimental group and four were in the control group, while six withdrew from the research. Members in both groups had their stump surfaces examined for the species of bacteria present at the time of prosthesis fitting. Members in the experimental group used the prostheses while those in the control group did not use the prostheses and both groups were re-examined three weeks later.  Results:  The use of prostheses generally increased the mean number of species of bacteria found on the skin surface of stumps of amputees three weeks after starting to use the artificial limbs although the increase was not found to be statistically significant. No significant change was observed in the mean number of species of bacteria in the control group at the time of prosthetic fitting and after the three weeks of disuse. This implied that the observed increase in bacterial load was truly due to the use of prostheses in the experimental group.  Conclusion: Escherichia coli, Staphylococcus aureus, Staphylococcus epidermidis, Streptococcus pyogenes, Clostridium tetani, and non-hemolytic streptococci were identified on the skin surfaces of the stumps of amputees.